Genome-wide scan of depressive symptomatology in two representative cohorts in the United States and the United Kingdom. (May 2018) - Mekli, Krisztina; Phillips, Drystan F.; Arpawong, Thalida E.; Vanhoutte, Bram; Tampubolon, Gindo; Nazroo, James Y.; Lee, Jinkook; Prescott, Carol A.; Stevens, Adam; Pendleton, Neil
Abstract: Unlike the diagnosed Major Depressive Disorder, depressive symptomatology in the general population has received less attention in genome-wide association scan (GWAS) studies. Here we report a GWAS study on depressive symptomatology using a discovery-replication design and the following approaches: To improve the robustness of the phenotypic measure, we used longitudinal data and calculated mean scores for at least 3 observations for each individual. To maximize replicability, we used nearly identical genotyping platforms and identically constructed phenotypic measures in both the Discovery and Replication samples. We report one genome-wide significant hit; rs58682566 in the EPG5 gene was associated (p = 3.25E-08) with the mean of the depression symptom in the Discovery sample, without confirmation in the Replication sample. We also report 4 hits exceeding the genome-wide suggestive significance level with nominal replications. Rs11774887, rs4147527 and rs1379328, close to the SAMD12 gene, were associated with the mean depression symptom score (P-values in Discovery sample: 4.58E-06, 7.65E-06 and 7.66E-06; Replication sample: 0.049, 0.029 and 0.030, respectively). Rs13250896, located in an intergenic region, was associated with the mean score of the three somatic items of the depression symptoms score (p = 3.31E-07 and 0.042 for the Discovery and Replication samples). These results were not supported by evidence in the literature. We conclude that despite the strengths of our approach, using robust phenotypic measures and samples that maximize replicability potential, this study does not provide compelling evidence of a single genetic variant's significant role in depressive symptomatology.